Internet Marketing for Banking services Comparison between BADR Bank – Algeria- and ADCB Bank –UAE- Marketing Internet pour services bancaires - Bouabdallah, Messaoud; Tchouar, Abdelkrim; Alshakary, kadri (Finance and Business Economies Review, 2019)
This research addresses the issue of Internet marketing, which is the new face of marketing. The aim of this research is to answer the main problem that revolves around the use of the Internet in the marketing of banking services by comparing between two of the leading banks in their countries, BADR Bank in Algeria and ADCB Bank in the United Arab Emirates. And the results of this research has revealed the importance of internet marketing, And perhaps the most important result reached by the research is to detect a significant disparity between the Internet marketing efforts of the two banks under study.